A STUDY OF THE RELATIONSHIP BETWEEN SELF-ESTEEM AND ACADEMIC ACHIEVEMENT IN MEDICAL STUDENTS OF SARI MEDICAL COLLEGE: Life Sciences-Medical Psychology - HADINEZHAD, PEZHMAN; MASOUDZADEH, ABBAS (International Journal of Life Science and Pharma Research, 2018)
The foundation of a healthy society is intellectually and physically healthy people. A society in which people do not have an appropriate level of physical and intellectual health, will not be a healthy society. However, in the meantime, medical students must be in a good condition in terms of mental health. A doctor who suffers from depression, anxiety, or addiction will never be able to fulfill his important task in society. A society in which the educated class, i.e. university students specially a group of the most talented students, i.e. medical students, have low self- esteem, will definitely face with numerous problems. The present study, investigates the relationship between self-esteem and academic achievement in medical students of Sari medical college.